Loss of CLN7 results in depletion of soluble lysosomal proteins and impaired mTOR reactivation. (5th March 2018) - Danyukova, Tatyana; Ariunbat, Khandsuren; Thelen, Melanie; Brocke-Ahmadinejad, Nahal; Mole, Sara E; Storch, Stephan
Abstract: Defects in the MFSD8 gene encoding the lysosomal membrane protein CLN7 lead to CLN7 disease, a neurodegenerative lysosomal storage disorder belonging to the group of neuronal ceroid lipofuscinoses. Here, we have performed a SILAC-based quantitative analysis of the lysosomal proteome using Cln7-deficient mouse embryonic fibroblasts (MEFs) from a Cln7 knockout (ko) mouse model. From 3335 different proteins identified, we detected 56 soluble lysosomal proteins and 29 highly abundant lysosomal membrane proteins. Quantification revealed that the amounts of 12 different soluble lysosomal proteins were significantly reduced in Cln7 ko MEFs compared with wild-type controls. One of the most significantly depleted lysosomal proteins was Cln5 protein that underlies another distinct neuronal ceroid lipofuscinosis disorder. Expression analyses showed that the mRNA expression, biosynthesis, intracellular sorting and proteolytic processing of Cln5 were not affected, whereas the depletion of mature Cln5 protein was due to increased proteolytic degradation by cysteine proteases in Cln7 ko lysosomes. Considering the similar phenotypes of CLN5 and CLN7 patients, our data suggest that depletion of CLN5 may play an important part in the pathogenesis of CLN7 disease. In addition, we found a defect in the ability of Cln7 ko MEFs to adapt to starvation conditions as shown by impaired mammalian target of rapamycin complex 1 reactivation, reduced autolysosome tubulation and increased perinuclear accumulation of autolysosomes compared with controls. In summary, depletion of multiple soluble lysosomal proteins suggest a critical role of CLN7 for lysosomal function, which may contribute to the pathogenesis and progression of CLN7 disease.